Pseudoaneurysm of the Common Carotid Artery in an Infant due to Swallowed Fish Bone - Moulion Tapouh Jean Roger; Fokou Marcus; Fongang Emmanuel; Moifo Boniface; Juimo Alain Georges (Case Reports in Radiology)
Carotid artery pseudoaneurysm is a rare condition, particularly in the paediatric population. Only about 30 cases of carotid artery aneurysms in infants have been published until now. This paper reports the case of a giant pseudoaneurysm of the left common carotid artery due to swallowed fish bone by an 8-year-old boy. This pseudoaneurysm was 5.5 cm transverse-diameter and resulted in severe respiratory distress. It was treated by resection and end-to-end anastomosis with satisfactory outcome after one-year follow-up. To the best of our knowledge, this is the largest carotid artery pseudoaneurysm ever described in children.